Look Upstream: Measurement for Innovation on the Upper Rio Negro of the Amazon Basin - Shaw, Kurt; da Silva, Rita de Cácia Oenning (Frontiers in Pediatrics, 2021)
The growth of the randomized controlled trial (RCT) as the “gold standard” for evaluation has justly been praised as an advance in the professionalization of social programs and projects, an “adoption of science.” (1, p.731) None the less, the emphasis on the RCT biases funding for projects that distribute private goods (2) and which focus on “low hanging fruit” in health, nutrition, and sanitation (3), simply because those areas lend themselves to the sort of measurement that works with RCTs. As a result, many project developers in the government and NGO sectors lament that a hegemonic focus on RCTs impedes creativity or new models that challenge traditional paradigms. This case study of CanalCanoa, a community video coaching project for indigenous parents of young children in the Rio Negro region of the Amazon Basin, offers techniques to measure for innovation. Instead of developing a new RCT for an extremely diverse population (27 ethnic groups) where traditional childcare methods are in historical flux because of urbanization, CanalCanoa measured variables shown by previous RCTs to be causally connected with positive development results. By researching the impact of the intervention on nutrition, language (multilingualism, use of traditional songs and stories), and social network expansion, CanalCanoa measured upstream indicators, thus mixing scientific rigor with an opportunity for innovation and providing important insight and reform of a theory of change.